Performance trends of seasoned Two Oceans Ultramarathon runners - Noll, Helena (Department of Health and Rehabilitation Sciences, 2021)
Background: Endurance running is known to be a prevalent sport, due to well-understood health benefits. Ultramarathon running, particularly in master athletes, has been increasingly popular. Various parameters of an individual's ability to participate in numerous such events have been explored. The performance trends of such seasoned runners have been of interest to identify trends that could influence participation and running career longevity. Aim To identify performance trends of seasoned ultramarathon runners across their Two Oceans Ultramarathon running careers. Specific Objectives The specific objectives were to 1) describe the profile of seasoned ultramarathon runners who have completed 20 or more Two Oceans Ultramarathon races, including sex, number of ultramarathons completed, medal category of peak performance and age at debut Two Oceans Ultramarathon; 2) to determine average performance, peak performance, worst performance and the pattern of improvement or decline in performance in seasoned ultramarathon runners over 20 years of race participation; 3) to determine differences in factors that may influence performance trends, such as sex, number of ultramarathons completed, medal category of peak performance and age at debut Two Oceans Ultramarathon; and 4) to determine the variation in ultramarathon performance based on the sex, number of ultramarathons completed, medal category of peak performance and age at debut Two Oceans Ultramarathon. Methods Data from 625 runners who completed 20 or more Two Oceans Ultramarathons were extracted from a publicly available website (www.twooceansmarathon.org). Finish times across their running careers were used to establish average race speeds, peak and worst performances, changes in performance over time, and coefficients of variation in performance. Groups were compared according to a) sex, b) number of Two Oceans Ultramarathons completed (20 or more than 20), c) age category of debut race, and d) medal category of peak performance. Results The finishing times and race speed results showed that males ran significantly faster than females across their 20 year Two Oceans Ultramarathon running careers (p=0.00001). Runners who completed more than 20 races had faster finishing times and race paces than those who ran 20 Two Oceans Ultramarathons (p=0.00001). When performances of the participants were analysed according to age categories, the youngest age group, namely 16-19, had the fastest average finishing times across 20 years of racing (p=0.00002). Peak and worst performances showed that best personal efforts were attained in the first quarter of the Two Oceans Ultramarathon career, and worst race performances toward the end of these running careers. It was observed that as running careers progressed over time, the groups compared showed a pattern of performance convergence as differences in finishing times and running speeds decreased. Discussion and Conclusion The findings of this study suggest that a decline in performance over time is a natural and inevitable progression of a running career. Peak performances are usually acquired within the first few years of running careers. Participation trends as well as improved performances of master runners has shown that advanced age may be favourable in successful long-term ultramarathon running. This study identified a unique cohort of athletes who have consistently maintained ultramarathon running for 20 or more years. There is an opportunity for more detailed investigation of factors contributing to the longevity of their running careers, with the goal of promoting continuity in endurance running participation and physical activity at large.